Diplomasi kesehatan: kerjasama indonesia dan amerika serikat dalam menangani wabah pes di boyolali 1968 - Iin Zubaidah; Refanda Pratiwi; Muhammad Hilmi Fauzi (Historiography: Journal of Indonesian History and Education, 2021)
This paper aims to determine the relationship of 'health diplomacy' between Indonesia and United States when dealing with the bubonic plague in Boyolali 1968. This study used historical research methods consisting of heuristic, source criticism, interpretation and historiography. The data were obtained through literature study of sources in the form of books, archives, and other literatures that are still relevant to the theme raised. The result of this study indicates that the steps taken by the New Order government in dealing with the plague were very different from what has been conducted by Soekarno. If Soekarno insisted on standing on his own feet in overcoming the epidemic and endemic that was happening in Indonesia, Soeharto opened a wide door for US to contribute in handling the bubonic plague in Boyolali 1968. The United States provided helps in the form of medical personnel, vaccines procurement and health equipments. It has concluded that the leadership change from Soekarno to Soeharto showed an own dynamic on the handling system of plague in Indonesia. Health diplomacy between Indonesia and the United States became a milestone in the return of harmony diplomatic relations between the two countries after it got deteriorated in the Old Order era.Tulisan ini bertujuan untuk mengetahui hubungan “diplomasi kesehatan” antara Indonesia dan Amerika Serikat ketika menangani wabah Pes di Boyolali pada 1968. Penelitian ini menggunakan metode penelitian sejarah yang terdiri dari heuristik, kritik sumber, interpretasi dan historiografi. Data-data diperoleh melalui studi pustaka terhadap sumber berupa buku-buku, arsip, dan literatur-literatur lain yang masih relevan dengan tema yang diangkat. Hasil penelitian ini menunjukan bahwa langkah yang diambil pemerintahan Orde Baru dalam menangani wabah amat berbeda dengan apa yang dilakukan oleh Soekarno. Jika Soekarno bersikeras untuk berdiri di atas kaki sendiri dalam mengatasi epidemi dan endemi yang tengah terjadi di Indonesia, Soeharto malah membuka pintu lebar bagi Amerika Serikat untuk ikut andil dalam menagani wabah Pes di Boyolali pada 1968. Amerika Serikat memberikan bantuan berupa tenaga medis, pengadaan vaksin, dan alat-alat kesehatan. Dapat disimpulkan bahwa pergantian kepemimpinan dari Soekarno ke Soeharto memperlihatkan dinamika tersendiri pada sistem penanganan wabah penyakit di Indonesia. Diplomasi kesehatan antara Indonesia dan Amerika Serikat menjadi tonggak kembali harmonisnya hubungan diplomatik kedua negara setelah sempat memburuk di era Orde Lama.